Effect of the double bond content of sizing agents on the mechanical properties of carbon fibre reinforced vinyl ester composites. (8th February 2022) - Cheng, Xianhe; Huang, Yuzhang; Fang, Quantao; Gao, Jingwei; Luo, Tianzhi; Zhou, Ying; Yang, Chuncai
Abstract: Unsaturated polyester sizing agents with various double bond contents have a significant influence on the interface between carbon fibers (CF) and vinyl ester resins (VER). This paper aims to study the effect of the double bond content of sizing agents on the surface properties of CF and thermo mechanical properties of the sized CF/VER composites. We synthesized five types of self-emulsifying cationic sizing agents with various double bond contents and characterized the samples by FTIR, dynamic light scattering (DLS), cryo-scanning electron microscopy (Cryo-SEM) and thermal gravimetric analysis (TGA). The double bond content of the sizing agents on the cross-linking extent of the CF surface were investigated on factors such as the wettability of VER, the interlaminar shear strength (ILSS) and flexural strength and modulus of CF/VER composites. It was identified that the distribution of the sizing agent emulsions had a mono-dispersion of around 50 nm and were thermally stable below 300 °C. Additionally, it was identified that the double bond content of the sizing agents enhanced the grafting reactions and cross-linking extent between the sizing agent and CF surface. The CF had the best wettability for vinyl ester resin when the double bond content was 10% in the sizing agent. In addition, the ILSS, the flexural strength and the modulus reached maxima. Graphical abstract: Image 1 Highlights: Novel unsaturated sizing agents with stable thermal properties were prepared. The thermal mass loss method was used to calculate the cross-linking extent of sized CF. The CF had the best wettability for VE resin at about 10% of the double bond content in the sizing agent. The interface shear strength between the CF and the VER was enhanced by 53%. The flexural modulus between the CF and the VER was enhanced by 49%.